KAJIAN FINANCIAL DISTRESS PADA BANK SYARIAH DI INDONESIA - Wardani, Hamukti Pramudya; Sarwono, Aris Eddy; Puji Astuti, Dewi Saptantinah (Universitas Slamet Riyadi, 2021)
The purpose of this study is to analyze the potential for financial distresswith the Altman Z-score Modification method in Islamic banks in Indonesia andanalyze the differences between Muamalat Bank and public banks that opensharia. The scope of this research is empirical study. The study population isIslamic banks in Indonesia. The sample was 11 years with a purposive samplingtechnique. Data collection methods use documentation and study of literature.Analycis data techniques using the Altman Z-Score modification. The resultsshowed that bankruptcy prediction with the Altman Z-Score Model modificationon Islamic banks in Indonesia that the majority of banks in healthy condition, in2011 and 2012 Bank Bukopin was predicted to go bankrupt, in 2014 Bank Jabarand Banten Syariah experienced potential bankruptcy then in gray area, BankSyariah Mandiri and Bank Panin Syariah experience potential bankruptcy. BankJabar and Banten Syariah in 2015 and 2017 are in the gray area and Bank PaninSyariah experiences potential bankruptcy while in 2018 it is in a gray area. Theresults showed that there were significant differences in financial distress andROA between Muamalat Bank and Other Sharia Commercial Banks.